F70 Early manifestation and rapid symptom progression in a case of homozygous trinucleotide expansion in the TBP-gene in autosomal dominant spinocerebellar ataxia type 17. (12th September 2022) - Forras, Patricia Vanda; Wilfling, Sibylle; Mrochen, Anne; Dufke, Claudia; Linker, Ralf; Hehr, Ute; Kohl, Zacharias
Abstract : Background: Spinocerebellar ataxia type 17 (SCA17) is a rare, autosomal-dominantly inherited neurodegenerative disease caused by a CAG/CAA repeat expansion in the TATA-box-binding protein (TBP) gene. Clinically, SCA17 is quite variable and includes cerebellar and hypokinetic-rigid symptoms, chorea as well as cognitive impairment. Thus, the disease is also called a Huntington disease phenocopy (HDL-4). Case History: A 39-year-old female patient presented with cognitive impairment and behavioural symptoms with affect lability and impulsivity that had been present since the age of 35 and had progressed rapidly over time. Clinical findings included stance and gait ataxia, saccadic gaze, chanting speech and generalized chorea. The family history was unremarkable. Brain imaging showed isolated cerebellar atrophy with normal visualisation of the basal ganglia. The molecular-genetic diagnostics for Huntington's disease was unremarkable. In the extended human genetic examination, a homozygous expanded allele with 44 CAG/CAA repeats in the TBP gene was detected, thus confirming the diagnosis of SCA17. Within 2 years, the patient showed a clear increase in cognitive changes and behavioural disturbance. Conclusions: In the present case, a homozygous expanded allele with 44 CAG/CAA repeats in the TBP gene leads to an early age of manifestation, in contrast to SCA17 patients with comparable heterozygous intermediate repeat expansions with reduced penetrance. Furthermore, the index patient showed faster progression of symptoms, suggesting that SCA17 homozygous trinucleotide expansions are associated with a more severe disease course even with intermediate repeat expansions.